The influence of F. Froebel’s ideas on the development of social childcare in the USA (Pedagogy of Higher and Secondary Education, 2013)
Klyushnikova T. А. The influence of F. Froebel’s ideas on the development of social childcare in the USA.The author of the article definds influence of F. Froebel’s ideas on the development of early childhood education in the USA and analyses work of S.Hall on pedagogy of kindergarten of the German educator.
Keywords: pedagogy of kindergarten; Froubel gifts; Froubel classes; S.Hall; USA; public preschool education; Froubel courses